The synergistic effect of salinity and water depth on soil properties and maize productivity under foliar application of potassium silicate - Abdeen, S. A. (International Journal of Agricultural Technology, 2021)
Soil salinity and water table depth are the most effective factors on soil features and crop productivity. The close relationship between salinity and water depth on soil characteristics, and maize productivity under foliar application of potassium silicate were investigated. The results showed that soil salinity and water table death in the studied sites were ranges between 1.27 to 5.30 dS.m-1 and ≤65cm to ≤90cm, respectively. Also, pH, EC and total N in water table were ranged between 7.64 to 8.3, 5.80 to 9.80dSm-1 and 25.5 to 56.40mg.l-1, respectively. Also, soil pH, OM and CEC, CaCO3, and ESP in the successive layers of the studied soil profiles were fluctuated between 7.02 to 7.71, 0.20 to 0.84 % ,3.80 to 8.0 cmolc kg-1, 1.21 to 2.81% and 7.5 to 14.16%, respectively. On the other side, the field capacity (FC), saturated hydraulic conductivity (Ksat) and bulk density (Bd) were ranged between 13 to 14.5% ,4.20 to 7.50 cm.h-1, and 1.55 to 1.70 Mg m-3, respectively. Addition that water table depth (≤65cm) in saline soil (˃4 dSm-1) reduced grain yield and chemical composition of maize as compared to water table depth (≤90cm) in non-saline soil (˂ 4 dSm-1). Foliar application of potassium silicate gave a significant increase in the chemical composition and grain yield of maize grains. Nitrogen, phosphorous, potassium and crude protein were ranged between 1.25 to 2.11 %, 0.20 to 0.32 %, 1.10 to 1.63 % and 8.13 to 13.90 %, respectively. Maize yield ranged between 2033 to 2313 kg.fed-1. The highest values were observed at non saline soil under 4% potassium silicate as compared to saline soil without application of potassium silicate. So, it was considerable that the potassium silicate can limited the side effect of soil salinity and water table